Improvement of the textural characteristics of curdlan gel by the formation of hydrogen bonds with erythritol. (August 2021) - Tao, Haiteng; Wang, Bozhuo; Wen, Haichao; Cui, Bo; Zhang, Zheng; Kong, Xiangping; Wang, Yuxiao
Abstract: The addition of sugar and polyols can enhance the structure of gels. To prevent the overconsumption of sugar, the polyol erythritol was used to investigate the gelation mechanism of curdlan gel, which is especially beneficial for diabetics. We found that with increased levels of erythritol, the textural characteristics of curdlan gels first increased and then decreased. The optimum level of erythritol was found to be 5% (w/w) using texture profile analysis (TPA). Additionally, the mixed curdlan and erythritol gel had increased freeze-thawing stability with high water holding capacity. The structures of curdlan/erythritol gels were further characterized by fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and molecular docking. FTIR displayed a peak of O–H vibration at 3268 cm −1 with red shifts for curdlan and blue shifts for erythritol, suggesting hydrogen bonding between curdlan and erythritol. XRD showed that the large crystal or crystalline region of the curdlan/erythritol gels near 2θ = 19°, which indicated that the good compatibility between curdlan and erythritol. SEM showed the addition of erythritol formed a skeleton structure with strengthened connection bonds. The molecular docking analysis confirmed the formation of intermolecular hydrogen bonds between erythritol and β-1, 3-D-glucan in single and triple helical structures. All results demonstrate erythritol is beneficial to improve the textural characteristics of curdlan gel by the formation of hydrogen bonds, creating a denser network. Graphical abstract: Image 1 Highlights: The addition of erythritol could improve the textural characteristics of curdlan gel. Erythritol could increase the freeze-thawing stability of curdlan gel. The interactions analysis of erythritol with single and triple helical β-1, 3-glucan. Erythritol strengthened the curdlan gel network via the formation of hydrogen bonds.